Courage Measure (CM) – Cross-Cultural Adaptation and Psychometric Properties for Brazilian Adolescents - Sandra Padilha; Maynara Priscila Pereira da Silva; Evandro Morais Peixoto; Peter J. Norton (Psychological Test Adaptation and Development, 2024)
Abstract: The objective of the study was to adapt the Courage Scale and estimate validity evidence based on content and internal structure. The study included 510 young people, between 14 and 19 years old. The results of the content validity coefficient suggested the adequacy of the content. Confirmatory factor analysis (CFA) was used to test three factor models, namely one-factor, two-factor, and the random intercept model. The results indicated that it is possible to measure courage through a factor, when the acquiescent response style is controlled, corroborating the theoretical perspective, given that the random intercept model adjusted well to the sample data. In other words, the findings indicate that the scale is capable of measuring courage in the Brazilian context and that acquiescence control is an important method in evaluating the construct.